The Effect of Temperature in Vertical Migration Behavior of Three Species Zooplankton - Al-Doori, Nibrass Lafta (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2016)
The present study included  the impact of the follow-up variation in the temperature of aqueous medium in the vertical migration behavior of different groups of Zooplankton, consisted species Cyclops vernalis, Daphnia magna, Diaptomus dilopatus, that have been grown in controlled in terms of light and pH laboratory conditions, so choosing temperature of respectively 16,20,24,28, and 32 ËšC. The result showed a clear change in the migration behavior of testing planktonic species, it was a negative relationship between temperatures arises and individual of D. magna in the water column.While being appositive relationship with individual of C. vernalis and the same with D. dilopatus. Also, the result revealed a different impact of transaction with different levels of temperature in swimming and activity of movement, as observed reduction in swimming and activity of movement for individuals of species D. dilopatus and C. vernalis when getting down to the bottom of the water, whenever the temperature rose, while the behavior of individuals of a species D. magna contract and characterize the maximum activity at higher temperatures.